Автентичні покрівельні техніки та їх вплив на архітектоніку традиційних будівель в українських Карпатах - Матійчук, М. (Народна творчість та етнографія, 2008)
The article is based on expeditionary materials and archive sources. The author attempts to analyse the independent aspects of traditional building of Transcarpathia oblast. The author focuses on the roof techniques which were common in Hutsulschina and Boykivschina and their influence on formation of the roof of the building.